(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article provides a brief overview of what the mathematical modeling and the mathematical models are and how the mathematical models are classified depending on various features they can be characterized with. The article is in no way a comprehensive guide of the topic since there are a big number of ways mathematical models can be classified in, but rather an introductory explanation of the extremely broad area of mathematical modelling. The material of the article is heavily influenced by the book [1].